Decentralized-participatory plant breeding - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
A participatory breeding project conducted in Syria with the objective of testing an alternative way to produce improved varieties of crops grown in marginal environments such as barley. The project uses decentralized selection as a methodology to fit crops to the physical (climate and management) environment. However, it incorporates farmers’ participation in the process as crop breeding based on decentralized selection can still miss its objectives if it does not consider their knowledge of the crops and the environment. Thus plant breeding is done to fit crops to the specific needs and uses of farming communities.